EVALUATING THE MOLECULAR INTERACTION OF SAMBUCUS PLANT BIOACTIVE COMPOUNDS TOWARD TNF-R1 AND TRAIL-R1/R2 AS POSSIBLE ANTI-CANCER THERAPY BASED ON TRADITIONAL MEDICINE: THE BIOINFOTMATICS STUDY - WIRA EKA PUTRA; MUHAIMIN RIFA’I (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Inducing the apoptosis signaling pathway is one of the favorable treatment to overcome cancer incidence. Current treatment showed the increasing usage of natural products as therapy. Thus, the present work aims to evaluate the molecular interaction of Sambucus plant bioactive compounds toward the TNF-R1 and TRAIL-R1/R2 as possible anti-cancer therapy through the computational study. Approximately 31 bioactive compounds of Sambucus plant were screened as potential ligands to bind the TNF-R and TRAIL-R1/R2 protein models. Molecular docking was performed to evaluate the interactive features of the ligands toward the apoptosis channels. In this present study, the results showed the Pro C1 was on the top with the lowest free binding energy on the interaction with TNF-R1, TRAIL-R1, and TRAIL-R2. Moreover, based on the computational prediction demonstrated that several bioactive compounds from Sambucus plant have similar residues in the interaction with TNF-R1, TRAIL-R1, and TRAIL-R2. The evidence from this study implied that Pro C1 that mostly found in Sambucus plant has therapeutic potency as the activator of apoptotic signaling pathways through the interaction with TNF-R1 and TRAIL-R1/R2.